(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2013)
The choice of territorial unit is becoming an important issue for the assessment and planning of recreational potential, in the frame of which the assessment should be done. A more convenient unit in a mountainous area can be a river basin. The upper and middle flow of the Akhuryan River were studied and estimated.